Integrasi Kecerdasan Buatan (AI) sebagai Solusi Inovatif dalam Manajemen Pendidikan Islam untuk Meningkatkan Kualitas Pembelajaran dan Efisiensi Pengelolaan - Yulia, Meri; Supratman, Supratman (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2025)
This study explores the integration of Artificial Intelligence (AI) as an innovative solution in the management of Islamic education, emphasizing a balance between technological advancement and the unique values and principles inherent to Islamic educational institutions. AI significantly enhances administrative efficiency by automating routine tasks such as student data management, scheduling, and resource allocation, thereby reducing human error and workload while enabling administrators to focus on strategic educational improvements. In the pedagogical context, AI supports adaptive and personalized learning tailored to students’ individual needs, promoting not only academic achievement but also critical thinking and spiritual growth aligned with Islamic holistic education. The application of AI also facilitates broader access to educational resources through varied digital formats, addressing geographical and infrastructural challenges. Nevertheless, the adoption of AI raises complex ethical, cultural, and religious issues, including privacy protection, algorithmic bias, and the risk of reducing human involvement in education. The study underlines the necessity of a collaborative and careful approach involving scholars, educators, and technologists to develop AI frameworks compliant with Islamic ethics and sharia principles. Successful implementation depends heavily on educators’ readiness and continuous professional development to harness AI effectively and ethically. This research synthesizes recent literature (2015–2025) to provide a comprehensive framework guiding policymakers and educational leaders in leveraging AI to create dynamic, ethical, and spiritually grounded Islamic education management systems. Ultimately, AI integration can transform Islamic education by enhancing efficiency and quality without compromising its foundational moral and spiritual values.